Brazil and Argentina: From conflict to nuclear cooperation - Maria Miranda de Freitas, Glória (2024)
This work will focus on the following passage from the state of conflict between Brazil and Argentina for the establishment of cooperation in developing nuclear technology for peaceful purposes. For this, we will discuss the conflict in the Basin Cisplatin, the particularities of individual actions in this area of technological development, the Treaty of Tlatelolco, the characteristics of foreign policy of both countries on this issue, the placement of local elites, as well as the ways in which the consolidation of cooperation in question and finally, the creation of the Brazilian-Argentine Agency for Accounting and Control of Nuclear Materials (ABACC), of paramount importance for the progress of such cooperation.